2016
DOI: 10.1111/andr.12188
|View full text |Cite
|
Sign up to set email alerts
|

Semen leukocytes and oxidative-dependent DNA damage of spermatozoa in male partners of subfertile couples with no symptoms of genital tract infection

Abstract: SUMMARYThe influence of seminal leukocytes on generation of oxidative damage to sperm DNA was here investigated on male partners of subfertile couples asymptomatic for a genital tract infection. The study included 111 ejaculates from men attending the Andrology Centre at University of L'Aquila. Semen leukocytes subset included round cells expressing pan-leukocyte CD45 antigen, monocyte/ macrophage lineage antigen CD14, and activated macrophages HLA-DR antigen. In conclusion, oxidative-dependent DNA damage in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 45 publications
3
32
1
Order By: Relevance
“…Few studies found that leukocytospermia produces high levels of cytokines such as IL-6 and TNF-a that lead to high levels of breakdown products of oxygen such as ROS which in turn resulting in lipid peroxidation. Eventually, this mechanism may lead to the impairment of sperm motility and loss of fertilizing potential (Du Plessis et al, 2015;Micillo et al, 2016;El-Sakka, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies found that leukocytospermia produces high levels of cytokines such as IL-6 and TNF-a that lead to high levels of breakdown products of oxygen such as ROS which in turn resulting in lipid peroxidation. Eventually, this mechanism may lead to the impairment of sperm motility and loss of fertilizing potential (Du Plessis et al, 2015;Micillo et al, 2016;El-Sakka, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is defined by the World Health Organization (Ford 2010) as ≥1 9 10 6 WBC/mL of semen and is present in 10% to 20% of infertile men (Ford, 2010). Leukocytes (polymorphonuclear neutrophils and macrophages) have important implications in male fertility as they mediate sperm damage, including DNA fragmentation, through the secretion of reactive oxygen species (ROS) (Micillo et al, 2016). Leukocytes (polymorphonuclear neutrophils and macrophages) have important implications in male fertility as they mediate sperm damage, including DNA fragmentation, through the secretion of reactive oxygen species (ROS) (Micillo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Moskovtsev, Willis, White, and Mullen (2007) showed a very weak effect of leucocytospermia on DNA impairment and concluded that the impact of leucocytes in the pathology of SDF may be less than thought originally. This lack of correlation between SDF and the number of seminal leucocytes was independently confirmed by three groups (Cohen-Bacrie et al, 2009;Henkel et al, 2005;Micillo et al, 2016).…”
mentioning
confidence: 82%
“…While some authors support the notion that chromatin impairment is ascribed to the compromised conventional sperm parameters (Micillo et al, 2016;Saleh et al, 2003;Varghese et al, 2009), DNA fragmentation is regarded as an independent measure of male fertility, irrespective of conventional sperm parameters (Evenson et al, 1999;Giwercman et al, 2010). While some authors support the notion that chromatin impairment is ascribed to the compromised conventional sperm parameters (Micillo et al, 2016;Saleh et al, 2003;Varghese et al, 2009), DNA fragmentation is regarded as an independent measure of male fertility, irrespective of conventional sperm parameters (Evenson et al, 1999;Giwercman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%